Wikihouse - Thermal performance modelling & life cycle assessment - Jim Parker; David Glew; Kami Rakhshanbabanari; Chris Gorse (2021)
The first section of this report (2.1) presents the results from a sensitivity analysis (SA) which quantifies the impact of three different variables on the thermal performance of the building. Variables considered include: four insulation products; four window types; and five levels of airtightness. The SA was designed to provide the Wikihouse design team with quantified data on which to base their selection of materials. The Heat Transfer Coefficient (HTC) of a dwelling quantifies the overall fabric performance independent of any differences in occupancy, heating systems or site location. The results from the SA show that the Wikihouse Skylark system can achieve similar HTC values as those in dwellings built to the Passivhaus standard when using triple glazing and the lowest airtightness targets. Once target performance values were identified through the SA, these were then used to model the annual energy and CO2 of two-bedroom designs for a two-storey house and a bungalow (section 2.2). To align with Real Living Homes’ initial area of development, the majority of this analysis focused on models using simulation weather files for the Leeds area. However, the dwellings were also modelled in other locations and in different orientations around the UK. Results show that the Wikihouse Skylark design would achieve considerable savings when compared to notional dwellings with fabric standards that meet the minimum required by Part L1A of the Building regulations. An LCA analysis showed that the Wikihouse had less than half the life cycle greenhouse gas (CO2eq) emissions of a conventional brick and block cavity wall house (built to the same fabric standards as the Wikihouse target performance values), when considering a 100-year assessment period.